2011
DOI: 10.1111/j.1467-9922.2011.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

English Language Learners and Academic Achievement: Revisiting the Threshold Hypothesis

Abstract: This nonexperimental study explored the predictive strength of English proficiency levels on academic achievement of middle school students in a sample of 17,470 native English‐speaking (NES) students, 558 English language learners (current ELLs), and 500 redesignated fluent English proficient students (former ELLs). Results of multilevel analyses indicated that after controlling for relevant student‐ and school‐level characteristics, former ELLs significantly outperformed current ELL and NES students in readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 63 publications
(233 reference statements)
3
66
0
Order By: Relevance
“…Yet dual-language learning might also result in greater science achievement. This is because, upon reaching a threshold of linguistic competence, bilingualism's greater cognitive demands are hypothesized to accelerate children's academic achievement growth (Ardasheva, Tretter, & Kinny, 2012;Kempert, Saalbach, & Hardy, 2011;Ricciardelli, 1992), resulting in compensatory achievement growth trajectories (Crosnoe, 2012;Reardon & Galindo, 2009).…”
Section: Possible Dynamics Of Science Achievement Gapsmentioning
confidence: 99%
“…Yet dual-language learning might also result in greater science achievement. This is because, upon reaching a threshold of linguistic competence, bilingualism's greater cognitive demands are hypothesized to accelerate children's academic achievement growth (Ardasheva, Tretter, & Kinny, 2012;Kempert, Saalbach, & Hardy, 2011;Ricciardelli, 1992), resulting in compensatory achievement growth trajectories (Crosnoe, 2012;Reardon & Galindo, 2009).…”
Section: Possible Dynamics Of Science Achievement Gapsmentioning
confidence: 99%
“…The transferability of L1 reading to L2 reading has been discussed with the center of the short-circuit hypothesis or the threshold hypothesis (Alderson, 1984;Clarke, 1980). Regardless of the crucial importance of the threshold hypothesis in L2 reading, empirical studies to test the hypothesis have been regrettably limited and the findings, to date, have been surprisingly conflicted each other (Ardasheva et al, 2011;August, 2006;Bernhardt & Kamil, 1995;Bossers, 1991;Carrell, 1991;Jiang, 2011;Lee & Schallert, 1997;Park & Chae, 2000;Pichette et al, 2003;Taillefer, 1996). The conflicting findings might be in part attributable to L2 readers' native language that was intricately interwoven with other confounding variables including proficiency level, reading task, and learning context, and in part attributable to the lack of research methods used to test the hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…ELLs from Pre-K through College experience language barriers when in U.S. education facilities, public schools, colleges and universities. A number of studies have indicated that the numbers of ELLs are expected to continue to rise (Ardasheva, Tretter, & Kinny, 2012; English language learners, n.d.; Fayon, Goff, & Duranczyk, 2010;Herbert, 2012;Russakoff & Foundation for Child, 2011). Russakoff and Foundation for Child (2011) cited Thomas and Collier (2002) which explained that by 2030, the ELL population in the U.S. school system would be at 40%.…”
Section: Introductionmentioning
confidence: 99%